Perlindungan Hukum Terhadap Wisatawan oleh Biro Perjalanan Wisata di Kabupaten Badung - Gusti Ngurah Agung Suryadewa; Ida Ayu Putu Widiati; I Wayan Arthanaya (Fakultas Hukum Universitas Warmadewa, 2019)
The government in collaboration with the tourism business world, including travel agents and the public, has an obligation to provide support for tourism activities to run safely and must always refer to the legal aspects as a form of protection in the field of tourism for tourists. This is because in Article 26 letter (d) of Law No. 10 of 2009 concerning Tourism is expressly stated that tourism entrepreneurs have an obligation in providing comfort, hospitality, and providing a sense of security to tourists. However, the Act does not explain in detail the responsibilities of the travel agency to tourists. This study discusses two problems, namely 1). What is the form of legal protection for tourists in travel in Badung Regency and 2). What is the responsibility of the travel agency for tourists in Badung Regency. The type of research used in this journal is empirical legal research is legal research that starts from the gap between das solen and das sein, where there is a gap between the theoretical situation and the legal facts that occur in society. The approach used is the sociology of law which also studies the interrelationship between law and other social phenomena. Regarding the form of legal protection for tourists in tourist trips in Badung Regency, namely by providing legal protection, comfort and security to tourists, including providing facilities for elderly and disabled tourists, and getting a safety guarantee in the form of insurance for activities that have high risk. The form of responsibility of a travel bureau if there is a problem with the comfort of tourists, the travel usually always anticipates by improving services and racing on business standards certification for the travel bureau.